If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (c + 1) * 2x = (c + 1) * x + 1 Reorder the terms: (1 + c) * 2x = (c + 1) * x + 1 Reorder the terms for easier multiplication: 2x(1 + c) = (c + 1) * x + 1 (1 * 2x + c * 2x) = (c + 1) * x + 1 Reorder the terms: (2cx + 2x) = (c + 1) * x + 1 (2cx + 2x) = (c + 1) * x + 1 Reorder the terms: 2cx + 2x = (1 + c) * x + 1 Reorder the terms for easier multiplication: 2cx + 2x = x(1 + c) + 1 2cx + 2x = (1 * x + c * x) + 1 Reorder the terms: 2cx + 2x = (cx + 1x) + 1 2cx + 2x = (cx + 1x) + 1 Reorder the terms: 2cx + 2x = 1 + cx + 1x Solving 2cx + 2x = 1 + cx + 1x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1cx' to each side of the equation. 2cx + -1cx + 2x = 1 + cx + -1cx + 1x Combine like terms: 2cx + -1cx = 1cx 1cx + 2x = 1 + cx + -1cx + 1x Combine like terms: cx + -1cx = 0 1cx + 2x = 1 + 0 + 1x 1cx + 2x = 1 + 1x Add '-2x' to each side of the equation. 1cx + 2x + -2x = 1 + 1x + -2x Combine like terms: 2x + -2x = 0 1cx + 0 = 1 + 1x + -2x 1cx = 1 + 1x + -2x Combine like terms: 1x + -2x = -1x 1cx = 1 + -1x Divide each side by '1x'. c = x-1 + -1 Simplifying c = x-1 + -1 Reorder the terms: c = -1 + x-1
| 7x^2+4x-25=0 | | 3(x+4)+5(2x-1)=8x+37 | | 6.1+x+7.8=19.4 | | 12a=24 | | X^2/1 | | 4x-5=K(x+1) | | 8x-6=5x+6 | | 8x-6x=5x+6 | | x-vsquad=wsquad | | 4x-15=x+45 | | x+x+4+x+4=50 | | -4z^2-4z-3=0 | | 1/2=m-18 | | P-5.6=-21.6 | | -2(x+4)=5(x-2)-26 | | x/6=26 | | 9t+2=-25 | | 2w-7/3 | | (6cosx-1)(cosx+1)=3 | | x^2+x-y+1=0 | | Q=50-0.5P+2I | | 7-4h+8+9h= | | 4-3k+5= | | content://0@media/external/file | | 6g+9-4g+20=34 | | 22x+2=10x+4 | | 7(2x+3)-3(5x-2)=5(3x-4)-3(3x-4) | | 0.25b+0.20b-3=15 | | 7y-23/4=1/2 | | 40-x/3=4 | | 2x-5+x=98 | | x+(x-1)=110 |